2018
DOI: 10.1007/s11270-018-3794-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Integrated Membrane Treatment on the Phytotoxicity of Wastewater from the Coke Industry

Abstract: In this paper, coke wastewater that had passed through biological and integrated membrane processes (filtration on sand bed—reverse osmosis) was chosen to assess the phytotoxicity of selected industrial wastewater with regard to the test plant—Vicia faba. An innovative research technique in vitro test was conducted in a large scale phytothrone chamber on two matrices: cotton and Murashige and Skoog Basal Medium (MSBM). The toxicity of wastewater was evaluated for samples: (1) treated in the treatment plant by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The basic tool for achieving this goal were the legal requirements developed practically in all countries regarding the conditions for wastewater discharge into receiving waters, which are systematically becoming stricter in terms of nutrient content (Bohman 2018 ; Preisner et al 2020b ). This forced the use of advanced technologies for their removal in complex and expensive wastewater treatment systems (Surratt and Aumen 2014 ; Smol et al 2018 ). It is a well-known fact that mainly the dissolved inorganic forms of nutrients are directly available to aquatic vegetation, while in rare cases, also some organic compounds (Czerwionka 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The basic tool for achieving this goal were the legal requirements developed practically in all countries regarding the conditions for wastewater discharge into receiving waters, which are systematically becoming stricter in terms of nutrient content (Bohman 2018 ; Preisner et al 2020b ). This forced the use of advanced technologies for their removal in complex and expensive wastewater treatment systems (Surratt and Aumen 2014 ; Smol et al 2018 ). It is a well-known fact that mainly the dissolved inorganic forms of nutrients are directly available to aquatic vegetation, while in rare cases, also some organic compounds (Czerwionka 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, especially high N values were observed, which in the river MZ ranged from 6.44 to 28.50 mg/L in terms of TN and from 3.63 to 20.10 mg/L in terms of N-NH 4 . Inorganic N forms such as highly bioavailable N-NH 4 are usually efficiently removed by the wastewater treatment processes (Farazaki and Gikas 2019;Kowalewski et al 2016;Smol et al 2018) since it causes oxygen deficiency in the wastewater receiver due to high oxygen demand for its oxidation (Fuhrmeister et al 2015). A study from China on urban river N pollution (Zhang et al 2015) confirms a sharp decrease in DO concentration with the increase of N-NH 4 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The phytotoxicity of coking wastewater treated with biological means showed higher germination inhibition in comparison to the sample treated with reverse osmosis (Smol et al 2018). The study highlighted the necessity of monitoring the toxicity degree of coking wastewater.…”
Section: Complexity and Toxicity Of Coking Wastewatermentioning
confidence: 94%
“…Interestingly, it was observed that photodegradation as an advance treatment increases the toxicity of wastewater on maize development. We can deduce from the studies that coking wastewater is one the most toxic industrial wastewaters, showing toxicity in all forms such as bio-toxicity, ecotoxicity, acute toxicity and genotoxicity (Zhou et al 2015;Na et al 2017;Smol et al 2018). Therefore, integrated advanced treatment using the physicochemical-biochemical combined process is necessary for reducing the toxicity of coking wastewater (Liu et al 2017b).…”
Section: Complexity and Toxicity Of Coking Wastewatermentioning
confidence: 99%